Effective environmental regulation in China : reflections on the experience of Europian Union legislation on environment permits - Pasini, Federico (New York: Routledge, 2021)
'Though recently improved, Chinese legislation on environmental permits is still weak and urgent measures are needed to help the country in moving towards an effective permitting system. This book examines this legislation gap and presents a contribution to solving China's pollution problems. By analysing the deficiencies of current Chinese provisions on permitting in light of international and EU legislation, in its Italian application, the book determines which permitting legislative structure and means China should embrace in practice, in order to build more comprehensive legislation on emission permitting. It is argued that a set of ad hoc legislative measures should be implemented so as to strengthen China's environmental protection and efficiently tackle pollution. The book will be a valuable resource for researchers, academics and policy-makers working in the areas of international environmental law and comparative law'--
Fundamentals of environmental permitting : from traditional to integrated regulatory approach -- The EU legislation on integrated environmental permits : scope, regulatory instruments and application of integrated pollution prevention control and industrial emission directives -- The application of IPPC and IED in Italy : towards the achievement of sustainable development -- Potential and constraints of China's regulatory framework on environmental permits -- Proposals to enhance effectiveness and ensure integration in the development of China's legislation on environmental permits -- Conclusion.
Includes bibliographical references and index. (253-258 pages)
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ OC/ Bookline Services
Keywords: Environmental permits -- China; Environmental permits -- European Union countries